Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

High-temperature episyenites from late-Variscan Sàrrabus pluton (SE Sardinia, Italy) - F. Secchi; S. Naitza; A.M. Conte; G. Oggiano; M. Casalini; M. Kohút; T. Giovanardi (Lithos, 2026)

Lowland tropical forests remain a methane sink under warming and long-term hurricane disturbance recovery - Gabriele Larocca Conte; Lucia Zuvela; Rachel Cruz-Pérez; Tatiana Barreto-Vélez; Nibia Becerra-Santillan; Sophia F. Campbell; Hieu P. Chu; Trung Dam; Iana F. Grullón-Penkova; Miriam Kleit; Deyaneira A. Ortiz-Iglesias; Laura C. Rubio-Lebrón; et al. (Agricultural and Forest Meteorology, 2026)

Towards a disease digital twin: Howard T. Odum's legacy for cancer biology and medicine - F. Surra; L. Conte; E. Cavarzerani; F. Rizzolio; A. Romano; F. Gonella (Ecological Modelling, 2025)

A Chromosome Inversion Creates a Supergene for Sex and Colour in Lake Malawi Cichlids - Kristen A. Behrens; Soumya Jailwala; Frances E. Clark; Anne C. Meyer; Nikesh M. Kumar; Adrianus F. Konings; Reade B. Roberts; Matthew A. Conte; Jeffrey T. Streelman; Patrick T. McGrath; Thomas D. Kocher (Molecular Ecology, 2025)
Cichlid fishes have the highest rates of evolutionary turnover of sex chromosomes among vertebrates. Many large structural polymorphisms in the radiation of cichlids in Lake Malawi are associated with sex chromosomes and may also carry adaptive variation. Here, we investigate the structure and evolutionary history of an inversion polymorphism that includes both a ZW sex locus and an orange‐blotch colour polymorphism in the rock‐dwelling cichlid fishes of Lake Malawi. We use long‐read sequencing to characterise the sequence and breakpoints of the inversion. We quantify allele frequency differences across the inversion in population samples of the genera Metriaclima and Labeotropheus . We also examine expression differences of genes in the inversion. The simple inversion spans 7 Mb and is flanked by CACTA transposons that may have catalysed the rearrangement. The region includes ~600 genes, several of which show large differences in expression. Some of these genes are candidates for the sex and colour phenotypes. This inversion is an accessible model system for studying the role of structural polymorphisms and sex chromosome turnover in the adaptive radiation of cichlids in the lakes of East Africa.

Enriched oil-in-water emulsions as bioactive agents for locust bean gum films: A comparative investigation - Rodrigo F. Gouvêa; Mariana G.C. Azevedo; Carlos A. Conte-Junior; Cristina T. Andrade (Food Bioscience, 2024)

Reappraisal of red clays in porcelain stoneware production: Compositional and technological characterization - Riccardo Fantini; Sonia Conte; Alessandro F. Gualtieri; Michele Dondi; Francesco Colombo; Mattia Sisti; Chiara Molinari; Chiara Zanelli; Rossella Arletti (Applied Clay Science, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Seismic mitigation of a benchmark twenty-story steel structure based on intermodal targeted energy transfer (IMTET) - Majdi Gzal; Juan E. Carrion; Mohammad A. AL-Shudeifat; Billie F. Spencer; Joel P. Conte; Alexander F. Vakakis; Lawrence A. Bergman; Oleg V. Gendelman (Engineering Structures, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Nature-based solutions for nutrient pollution control in European agricultural regions: A literature review - A. Rizzo; C. Sarti; A. Nardini; G. Conte; F. Masi; A. Pistocchi (Ecological Engineering, 2023)

San Quirce (Palencia, Spain): new chronologies for the Lower to Middle Palaeolithic transition of south‐west Europe - Marcos Terradillos‐Bernal; Martina Demuro; Lee J. Arnold; Jesús F. Jordá‐Pardo; Ignacio Clemente‐Conte; Alfonso Benito‐Calvo; J. Carlos Díez Fernández‐Lomana (Journal of Quaternary Science, 2023)
San Quirce is an open‐air archaeological site situated on a fluvial terrace in the Duero basin (Palencia, northern Iberia). This paper presents new and consistent chronologies obtained for the sedimentary sequence using post‐infrared infrared stimulated luminescence (pIR‐IR) dating of K‐feldspars and single‐grain thermally transferred optically stimulated luminescence (TT‐OSL) dating of quartz. The new dating results indicate that the sequence is older than ~200 000 years and place San Quirce Level III within marine isotope stages (MIS) 8 and 7, between 274 ± 13 ka and 238 ± 13 ka. The main lithic assemblage at San Quirce comes from Level III. The predominant tool types found in this level are hammerstones, manuports and flakes, with a small proportion of cores and a significant presence of denticulates. Adaptation to local environmental conditions resulted in distinctive cultural habits, which were embedded in the cultural tradition of hominins occupying the site during the final third of the Middle Pleistocene. San Quirce preserves a simple cultural tradition that was employed by local hominins to engage in a diverse array of activities, and highlights the cultural diversity that appears to have been a characteristic feature of the Lower to Middle Palaeolithic transition 300–200 ka.

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Micro-climatic investigation and particulate detection in indoor environments: the case of the historical museum of Bersaglieri in Rome - A. Marcelli; M. Sebastianelli; A. Conte; F. Lucci; G. Della Ventura (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Effect of Restraining the Base of Support on the Other Biomechanical Features in Patients with Cerebellar Ataxia - C. Conte; Mariano Serrao; L. Cuius; A. Ranavolo; S. Conforto; F. Pierelli; L. Padua (The Cerebellum, 2018)

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

In situ remediation of contaminated marinesediment: an overview - G. Lofrano; G. Libralato; D. Minetto; S. De Gisi; F. Todaro; B. Conte; D. Calabrò; L. Quatraro; M. Notarnicola (Environmental Science and Pollution Research, 2017)

Is there an association between prior anti-inflammatory drug exposure and occurrence of peritonsillar abscess (PTA)? A national multicenter prospective observational case–control study - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Tooth agenesis and orofacial clefting: genetic brothers in arms? - M. Phan; F. Conte; K. D. Khandelwal; C. W. Ockeloen; T. Bartzela; T. Kleefstra; H. van Bokhoven; M. Rubini; H. Zhou; C. E. L. Carels (Human Genetics, 2016)

Peritonsillar abscess (PTA): clinical characteristics, microbiology, drug exposures and outcomes of a large multicenter cohort survey of 412 patients hospitalized in 13 French university hospitals - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Genetic diversity of the rare and endangered meadow violet ( Viola pumila Chaix) at the southern margin of its range - F. Buldrini; L. Conte; D. Dallai; C. Ferrari (Plant Biosystems, 2013)

Plasmid-mediated fluoroquinolone resistance determinants in Escherichia coli from community uncomplicated urinary tract infection in an area of high prevalence of quinolone resistance - C. Longhi; M. P. Conte; M. Marazzato; V. Iebba; V. Totino; F. Santangelo; C. Gallinelli; L. Pallecchi; E. Riccobono; S. Schippa; A. Comanducci (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Classification of the geographical origin of Italian donkey's milk based on differences in inorganic anions - G. Di Bella; V. Lo Turco; A.G. Potortì; R.R. Luppino; V. Fotia; F. Conte; G. mo Dugo (Food Additives & Contaminants: Part A, 2012)

Potential allelopathic activity of Sideritis italica (Miller) Greuter et Burdet essential oil - A. Basile; R. C. Cobianchi; D. Rigano; F. Senatore; M. Bruno; S. Rosselli; B. Conte; S. Sorbo (Plant Biosystems, 2011)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

Animal Welfare Labelling and the Approach of the European Union: An Overview on the Current Situation - Annamaria Passantino; F. Conte; M. Russo (Journal of Consumer Protection and Food Safety, 2008)

Expression Profile of Lgi1 Gene in Mouse Brain During Development - Patrícia A. O. Ribeiro; Lourenço Sbragia; Rovilson Gilioli; Francesco Langone; Fábio F. Conte; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2008)

Organochlorine pesticides and polychlorinated biphenyl residues in reared and wild Dicentrarchus labrax from the Mediterranean Sea (Sicily, Italy) - V. Lo Turco; G. Di Bella; L. La Pera; F. Conte; B. Macrí; G. mo Dugo (Environmental Monitoring and Assessment, 2007)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Genetic and phytochemical difference between some Indian and Italian plants of Withania somnifera (L.) Dunal - P Scartezzini; F Antognoni; L Conte; A Maxia; A Troìa; F Poli (Natural Product Research, 2007)

Effects of 5 Hz subthreshold magnetic stimulation of primary motor cortex on fast finger movements in normal subjects - R. Agostino; E. Iezzi; L. Dinapoli; F. Gilio; A. Conte; F. Mari; A. Berardelli (Experimental Brain Research, 2007)

Excitatory and inhibitory after-effects after repetitive magnetic transcranial stimulation (rTMS) in normal subjects - F. Gilio; A. Conte; N. Vanacore; V. Frasca; M. Inghilleri; A. Berardelli (Experimental Brain Research, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Topiramate and cortical excitability in humans: a study with repetitive transcranial magnetic stimulation - M. Inghilleri; F. Gilio; A. Conte; V. Frasca; C. Marini Bettolo; E. Iacovelli; B. Gregori; M. Prencipe; A. Berardelli (Experimental Brain Research, 2006)

Effects of repetitive transcranial magnetic stimulation in a patient with fixation-off sensitivity - O. Mecarelli; B. Gregori; F. Gilio; A. Conte; V. Frasca; N. Accornero; M. Inghilleri (Experimental Brain Research, 2006)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Synaptic potentiation induced by rTMS: effect of lidocaine infusion - M. Inghilleri; A. Conte; V. Frasca; F. Gilio; C. Lorenzano; A. Berardelli (Experimental Brain Research, 2005)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)

Research on Bacteraemia in Cultured Rainbow Trout - A. Panebianco; A. Giuffrida; F. Conte; G. Ziino; A. Minniti; L. Iannuzzi (Veterinary Research Communications, 2004)

Fogging can control Tetranychus urticae on greenhouse cucumbers - C. Duso; F. Chiarini; L. Conte; V. Bonora; L. Dalla Mont; S. Otto (Journal of Pest Science, 2004)

Antiepileptic drugs and cortical excitability: a study with repetitive transcranial stimulation - M. Inghilleri; A. Conte; V. Frasca; A. Curra’; F. Gilio; M. Manfredi; A. Berardelli (Experimental Brain Research, 2004)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Severe 5-fluorouracil toxicity associated with a marked alteration of pharmacokinetics of 5-fluorouracil and its catabolite 5-fluoro-5,6-dihydrouracil: a case report - Bocci G.; Danesi R.; Allegrini G.; Innocenti F.; A. Di Paolo; Falcone A.; Conte P.; M. Del Tacca (European Journal of Clinical Pharmacology, 2002)

Spread of electrical activity at cortical level after repetitive magnetic stimulation in normal subjects - Lorenzano C.; Gilio F.; Inghilleri M.; Conte A.; Fofi L.; Manfredi M.; Berardelli A. (Experimental Brain Research, 2002)

Bactericidal effect of pefloxacin and fosfomycin againstPseudomonas aeruginosa in a rabbit endocarditis model with pharmacokinetics of pefloxacin in humans simulated in vivo - D. Bugnon; G. Potel; Y. Q. Xiong; J. Caillon; D. Navas; C. Gras; M. F. Kergueris; P. Le Conte; F. Jehl; D. Baron; H. Drugeon (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)